2010
DOI: 10.4142/jvs.2010.11.4.321
|View full text |Cite
|
Sign up to set email alerts
|

Detection ofEscherichia coliO157 andEscherichia coliO157:H7 by the immunomagnetic separation technique andstx1andstx2genes by multiplex PCR in slaughtered cattle in Samsun Province, Turkey

Abstract: This study was conducted to investigate the presence of Escherichia (E.) coli O157 and E. coli O157:H7 and stx1 and stx2 genes on cattle carcasses and in rectal samples collected from Samsun Province of Turkey. A total of 200 samples collected from cattle carcasses and the rectal contents of 100 slaughtered cattle from two commercial abattoirs were tested using the immunomagnetic separation technique and multiplex PCR methods. E. coli O157 and E. coli O157:H7 were detected in 52 of the 200 samples (26%) tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
2

Year Published

2013
2013
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 38 publications
3
19
2
Order By: Relevance
“…However, in some of these studies the presence of shiga toxin producing E. coli O157 was examined. In the study by Inat and Siriken 13 conducted in Samsun city, the authors reported they had isolated STEC O157 from 18% of the rectal swab samples taken from 100 slaughtered cattle. In the study conducted by Aslantas et al 11 in Hatay city, it was reported that in 11% of 565 cattle faecal samples, STEC O157 was detected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in some of these studies the presence of shiga toxin producing E. coli O157 was examined. In the study by Inat and Siriken 13 conducted in Samsun city, the authors reported they had isolated STEC O157 from 18% of the rectal swab samples taken from 100 slaughtered cattle. In the study conducted by Aslantas et al 11 in Hatay city, it was reported that in 11% of 565 cattle faecal samples, STEC O157 was detected.…”
Section: Discussionmentioning
confidence: 99%
“…In studies conducted in several regions of Turkey, it is reported that E. coli O157 was detected in cattle faeces with rates varying between 0.6% and 25% [10][11][12][13] . However, in some of these studies the presence of shiga toxin producing E. coli O157 was examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All the extracted DNA of the standard strains and of the sample isolates were examined using multiplex PCR for molecular typing of the virulence genes (rfbE, stx1, stx2, fliC) using spesific nucleotide primers are listed in Table 1 (Hu et al, 1999). Amplification condition was carried out according to Inat and Siriken (2010) with a modification. The reaction mixture consisted of 4.8 µL of aquadest (DNAse, RNAse free), 10 µL of Maxima hot start green PCR master mix (2x) (Thermo Scientific™), and 0.4 µL of each primer.…”
Section: Characterization Of Stecmentioning
confidence: 99%
“…Therefore, at present no information is available about pathogenic bacteria, especially STEC contamination in Qurban festival. Cattle are the main reservoir of STEC, where the organism typically colonizes the lower gastrointestinal tract and shed the bacteria through their feces (Inat & Siriken, 2010;Perera et al, 2015). Also, cattle has a significant proportion of beef become contaminated during slaughter (Kundu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%